Stimulate no desenvolvimento de mudas de Kunquat ‘Nagami’ - Tecchio, Marco Antonio [UNESP]; Leonel, Sarita [UNESP]; Dos Reis, Luis Lessi [UNESP]; Simonetti, Lilian Massaro [UNESP]; Da Silva, Marlon Jocimar Rodrigues [UNESP] (My University, 2015)
The objective of this study was to evaluate the effect of Stimulate® on growth of ‘Nagami’ Kunquat seedlings in a greenhouse at the Horticulture Department in the College of Agricultural Sciences, UNESP. The seedlings of ‘Nagami’ Kunquat (Fortunella sp) grafted onto ‘Rangpur’ lime (Citrus limonia Osbeck) were from a commercial seedling nursery of citrus in Jacuba city-SP and were at 30 days after grafting. At 60 days after grafting, when the seedlings reached 40 cm mean height and 22 leaves, a total of four applications of Stimulate® plant growth regulator were performed in the following concentrations: 0, 50, 100, 150 and 200 mL L-1 of solution. Seedling growth evaluations were performed at 7, 14 and 21 days after the last Stimulate® application. The following variables were evaluated: plant height, number of leaves, above ground fresh and dry matter, fresh and dry matter of roots, length of roots, diameter of the rootstock and canopy stems, leaf area and the relative chlorophyll index. The application of 200 mL Stimulate® L-1 in ‘Nagami’ Kunquat seedlings led to an increase in plant height, number of leaves, root length and stem diameter of canopies.
Effect of stimulate® on growth of ‘Nagami’ Kunquat seedlings
Keywords: Fortunella sp; Plant growth regulator; Seedling nursery